Manfaat Penyaluran Bantuan Pangan Non Tunai (BPNT) dalam Mendukung Ketahanan Sosial Masyarakat Di Desa Blawi Kecamatan Karangbinangun Kabupaten Lamongan - Maghfiroh, Nita Lailatul (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the benefits of the distribution of Non-Cash Food Assistance (BPNT) in supporting the social resilience of the community in Blawi Village, Karangbinangun District, Lamongan Regency. consisting of 5 people, namely 1 village official and 4 BPNT beneficiary communities. This study found that BPNT contributes to improving the quality of life of the community, this program was designed by the government to increase food access for underprivileged families through non-cash mechanisms. The research method used is descriptive qualitative, with data collection through interviews, observations, and documentation. The results of the study show that BPNT provides benefits to the social resilience of the community, the benefits of BPNT to community resilience as follows, encouraging solidarity relationships with the community, providing hope for beneficiary families (KPM), and economically helping family food needs. With this program to improve the quality of life. First, this program increases community access to nutritious food, thus contributing to improving nutritional status, especially for children and pregnant women. Second, BPNT strengthens the economic resilience of the community by encouraging shopping at local stores, which in turn increases the income of small business actors. Third, this program strengthens social solidarity within the community, where beneficiaries support each other and share information about how to utilize the assistance.